PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, SISA LEBIH PEMBIAYAAN ANGGARAN DAN BELANJA DAERAH TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAMBI - Iqbal Kinanta Putra; Sri Rahayu; Rita Friyani (POLITEKNIK LP3I JAKARTA, 2024)
Regional government financial performance is the level of achievement of work results in the field of regional finance and a tool that can be used to record, measure, assess and achieve effective and efficient implementation of regional financial management. This research aims to examine the influence of local original income, balancing funds, excess budget financing and regional expenditure on the financial performance of district/city regional governments in Jambi province for the 2018-2022 period. The data used is secondary data obtained from the Jambi Province DJPK website and the total data is 55 from 11 district/city samples obtained using non-probability sampling techniques. The results of the research reveal that the regional original income variable has a positive effect on the financial performance of regional governments and the remaining variables over budget financing and regional expenditure have a negative effect on the financial performance of regional governments, but the balancing funds variable has no effect on the financial performance of regional governments. The results of this research indicate the importance of increasing regional funds in improving government performance and services to the community. Keywords: Regional Original Income, Balancing Funds, Excess Budget Financing, Regional Expenditures, Regional Government Financial Performance.